NEUROEDUCATION AND BILINGUALISM: HOW LEARNING IN TWO LANGUAGES INFLUENCES A CHILD’S BRAIN DEVELOPMENT - Kachur, Viktoriia (SWorldJournal, 2025)
The article focuses on how bilingual learning impacts child brain development in the context of neuroeducation, exploring the neurobiological mechanisms involved in the perception and processing of language signals during early childhood. The aim of the s